Cross-sectional study on prevalence and consequences of screen time on physical and mental health in children in the era of COVID-19 - Thakur (Rai), Neha; Singh, Arvind Kumar; Rai, Narendra; Shukla, Devesh Kumar (Asian Journal of Medical Sciences, 2022)
Background: With the ongoing growth and expansion of digital media and COVID-19 pandemic, children are inclining more and more toward spending time on digital media as compared to outdoor sports, leading to poor physical and mental growth. Developed nations have already set up a screen time guideline which is yet to be established in developing nations. This study was conducted with the objectives of identifying the needs of screen time guidelines and to study the impact of screen time on mental and physical health in children. Aims and Objectives: This study aims to check the screen time in children aged 2–18 and find the health consequences both physical and psychological in those children. Materials and Methods: A cross-sectional study on children aged 2–18 years was conducted between 2019 and 2020. Parents were asked to fill a pre-structured questionnaire. Impact on health physical and mental were assessed by pediatrician and psychologist. Results: A total of 155 children were enrolled in the study. Mean child hours in children aged 2–5 years, 5–10 years, and 10–18 years were 4 h, 5.83 h, and 6.29 h on week days and 5.64 h, 5.76 h, and 7.69 h on weekends, respectively. More than one-third of children had age of onset of screen time below 2 years of age. About 70% of children had malnutrition. Only 18% of parents were aware of concept of screen free days. Screen time had negative impact on health (P=0.0001) and on behavior of child (P=0.001). Average increase in screen time during COVID-19 was nearly 3 times the pre-COVID era. Conclusion: This study has paved the way for the need of larger study and development of guidelines on impact of screen time on children in developing nations where screen time guidelines is yet to be set more so in era of COVID 19 pandemic.